Central bank asset purchases and auction cycles revisited: New evidence from the euro area - Federico M. Ferrara (European Central Bank (ECB), 2024)
This study provides new evidence on the relationship between unconventional monetary policy and auction cycles in the euro area. Using proprietary data on purchases of public sector securities implemented by the Eurosystem, the paper examines the flow effects of asset purchase programmes on 10-year government bond yields in secondary markets around dates of public debt auctions. The findings indicate that Eurosystem's asset purchase flows mitigate yield cycles during auction periods and counteract the amplification impact of market volatility. The dampening effect of central bank asset purchases on auction cycles is more sizeable and precisely estimated for purchases of securities with medium-term maturities and in jurisdictions with relatively lower credit ratings. The analysis has broader implications for monetary policy and market functioning in the euro area.
Keywords: E52; E58; G12; G14; 330; Unconventional monetary policy; Public debt auctions; Bond yields; Flow effects; Eurosystem